2019
DOI: 10.1177/2329488419828808
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Communication on Internal Digital Platforms, Emotional Capital, and Corporate Performance: The Case for Leader-Centric Listening

Abstract: This research examined the role of leadership communication on internal digital platforms and the nature of digital listening by leaders. A survey of managers showed that in higher emotional capital (employees' aggregate feelings of goodwill toward a company and the way it operates) and higher performing organizations, leaders are much more active communicators on internal digital platforms. A critical incident study explored the nature of digital listening by leaders, showing that effective digital listening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 51 publications
0
31
0
1
Order By: Relevance
“…Supervisory leadership communication represents a major component of an organization’s internal communication system ( Men & Bowen, 2017 ). Findings from previous research suggest that supervisory communication styles, channels, skills, and effectiveness can influence employee attitudes, behaviors, emotional capital, and organizational performance ( Cardon et al, 2019 ; De Vries et al, 2010 ; Men, 2014 )), including employee trust ( Burke et al, 2007 ). To fill the aforementioned research gap and explore the impact of supervisory leadership communication on employee trust during the pandemic, this study incorporates motivating language theory (MLT).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Supervisory leadership communication represents a major component of an organization’s internal communication system ( Men & Bowen, 2017 ). Findings from previous research suggest that supervisory communication styles, channels, skills, and effectiveness can influence employee attitudes, behaviors, emotional capital, and organizational performance ( Cardon et al, 2019 ; De Vries et al, 2010 ; Men, 2014 )), including employee trust ( Burke et al, 2007 ). To fill the aforementioned research gap and explore the impact of supervisory leadership communication on employee trust during the pandemic, this study incorporates motivating language theory (MLT).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, projects and teams need this new collaborative technology (Matthiesen and Bjorn, Stray et al) [113], which goes beyond the classic video conferencing software that is often used for distributed meetings. The number of communication tools and platforms has increased substantially in recent years (Cardon and Marshall, Cardon, Huang and Power) [115], [116] An interesting application of technology for virtual and distributed teams is the electronic task board. Some of these are based on Kanban, which was successfully used by Toyota in factories in the 1950s.…”
Section: • Study the Adoption Of New Collaborative Technologies As Wmentioning
confidence: 99%
“…Therefore, as other authors have suggested (Avolio et al, 2000;Avolio and Kahai, 2003a,b;Dasgupta, 2011;Cortellazzo et al, 2019), leadership is currently developing through the "intermediation" of new ICTs, the presence and usage of which call for a change in the way leadership is practiced. These technologies include the internet, the intranet, e-mail, instant messaging, video conferencing systems, groupware systems, text messages, blogs, document sharing, smart apps, and social media (Avolio et al, 2001;Kissler, 2001;Zaccaro and Bader, 2003;Darics, 2020), all of which are now widespread in almost every working context (Cardon et al, 2019;Roman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%